Pengaruh Sumber Daya Alam (SDA) Dan Sumber Daya Manusia (SDM) Terhadap Pembangunan Ekonomi Di Kota Medan - Khairunnisa Khairunnisa; Maryam Batubara; Atika Atika (LPPM Universitas Labuhanbatu, 2024)
To determine the effect of natural resource potential (SDA) in improving economic development. To determine the influence of potential Human Resources (HR) on economic development. To determine the effect of the potential of Natural Resources (SDA) and Human Resources (HR) together on economic development in Medan. The research design is quantitative associative research. The type of Data in this study is quantitative data. Data analysis techniques in this study is descriptive analysis using software applications SPSS (statistical Product and Service Solution). Based on the results of the study the independent variable of Natural Resources (X1) has a positive and significant effect on economic development in Medan, the independent variable of human resources (X2) has a positive and significant effect on economic development in Medan, based on the results of the F test conducted, it is known that natural resources, human resources together or simultaneously have a significant effect on economic development in Medan.